Алгоритми ітераційного квадратичного програмування для задач оптимального розподілу потоків - Кірік, О.Є. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2008)
The quadratic programming problem which serves as an auxiliary one in the solution of nonlinear flow distribution problems is reduced to an unconstrained dual problem with a continuously-differentiable piecewise quadratic objective function. Instead of maximization of this implicit function, consecutive maximization of the specific quadratic functions is developed. These functions are constructed in such a way that at the end of the iterative procedure, the coincidence of the obtained solution with the maximum point of the dual problem can be arhieved.